The effectiveness of biological control of Frankliniella occidentalis in prevention of the spread of Tomato spotted wilt virus - Gillespie, Dianna L. (Kansas State University, 2009)
A two-year greenhouse experiment was conducted to compare the relative effectiveness of biological control versus chemical control for western flower thrips, Frankliniella occidentalis, as a means of reducing the spread of Tomato spotted wilt virus (TSWV) on tomatoes. To compare efficacy of different thrips management tactics for reducing TSWV incidence, tomatoes were subjected to one of three treatments: 1) biological control based on weekly releases of the predatory mite, Amblyseius cucumeris, at a commercially-recommended rate, 2) a single chemical treatment with Conserve®, a spinosad formulation, or 3) no treatment. TSWV was introduced into the greenhouse either by starting with 20% of the crop already infected and releasing non-viruliferous thrips, or by making a single release of viruliferous thrips. Analyses were done among thrips management tactics for each virus introduction method to examine the cumulative number of weeks plants were infected, the weekly proportion of infected plants, and total marketable yield. The effects of different virus introduction methods were also compared. A comparison of virus introduction methods showed that, among all plants, the average number of weeks they were infected by TSWV was significantly lower when virus was introduced through infected plants than by infected thrips. In addition, when virus was introduced by infected thrips, a significantly greater proportion of plants were infected in any given week than when virus was introduced on infected plants. Finally, crop yields were significantly lower when virus was introduced via infected thrips than on infected plants. Among thrips management methods, plants were infected for significantly less time, and the proportion infected was lower in any given week, when biological or chemical control was applied compared to no thrips management. Tomato yields were not affected by thrips management tactic. There was no significant difference between biological and chemical control in the length of time that plants showed symptoms. However, the proportion of infected plants was marginally greater with biological control in weeks 4 and 5 than with chemical control; differences were not significant thereafter. My findings suggest that inundative releases of biological control may provide as adequate a level of protection from TSWV as chemical control in commercial greenhouse tomato crops.
Keywords: Tospovirus; Biological control; Western flower thrips; Tomato spotted wilt virus; Agriculture, Plant Pathology (0480); Biology, Entomology (0353)